Women Workers in Essential British Metal and Chemical Industries during the Second World War and the Immediate Post-war Years - Robert A. Hart; J. Elizabeth Roberts (Institute of Labor Economics (IZA), 2023)
Group 1 metal and chemical industries formed the essential suppliers of British war materials during WW2. Their industrial sectors covered metal manufacture, general and electrical engineering, vehicle production, aircraft production, shipbuilding, metal goods, chemicals and explosives, and scientific instruments. Due mainly to almost 4 million men joining the armed forces, acute labour shortages necessitated women's recruited in large numbers. Women workers accounted for 16% of total Group 1 employment in 1939 rising to a peak of 37% in 1943. We use Ministry of Labour statistics on total annual numbers of female and male employees between 1937 and 1960. We examine in detail women's recruitment, training, skill growth as well as firms' radical changes to production methodologies to accommodate lower average women's skills. We compare female and male employment during the wartime transition period 1944 to 1947, followed by the period 1948 to 1960. Explanations are given for the decline and rise of female fortunes in the two periods. The employment data allow us to compare women's war-time and peace-time activities at industrial section-levels - e.g. repair of aircraft, iron and steel melting, explosives manufacture. The analysis includes wartime metal working data of the Engineering Employers' Federation (EEF). This allows us to widen our analysis. Among other features we use (1) female/male pay differentials to proxy the growth of women's skill attainments, and (2) differentiate between piecework and timework to compare employment advantages of incentivised payments contracts versus fixed short-run wage contracts.
Keywords: J16; J24; J31; N44; 330; women workers; Group 1 industries; skill acquisition; pay differentials